Socialization of Increasing Community Participation in the Supervision of Spatial Planning in the Riverside Area of Makassar City - Mujahid, Laode Muh Asfan; Akil, Arifuddin; ., Ihsan; Ali, Mukti; Ekawati, Sri Aliah; Irfan, Muhammad; Mirza, Muhammad Rio; ., Renaldi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The supervision of spatial plans should not only be imposed by certain agencies, but involve all elements of society. Community participation in spatial planning supervision has not gone well so far. This is indicated by the lack of community participation in spatial planning supervision, especially in vulnerable areas such as riverbanks. The purpose of this activity is expected to increase community knowledge in spatial planning supervision and is expected to actively participate in the spatial planning supervision agenda. In addition, it is hoped that the level of public awareness can increase so that they can play a direct role in spatial supervision in their area. The target of this activity is the community on the banks of the Tallo River in Makassar City. The activities were carried out through lectures and material exposure and also continued with activity evaluation. Evaluation was carried out before and after the implementation of the activity to determine the level of understanding of the participants and also measure the extent of their involvement in spatial planning supervision. The results of this activity showed an increase in participants' understanding of spatial planning from 86.7% (26 people) to 93.33% (28 people), in addition there was also an increase in the participants' desire to be involved in spatial monitoring activities to 100% (30 people) from 90% (27 people) who had never participated in spatial planning monitoring activities.